The concept and calculation of net benefits from goats in Ethiopian smallholdings - Ayalew, W.; Rischkowsky, Barbara A.; King, J.M. (2004)
Low adoption rates of introduced technologies in spite of manifestly increased production suggestthat livestock developer and farmer value livestock differently. The purpose of this paper is torelate productivity more closely to the perspective of the farmer. The concept of productivity isreviewed from growth/lactation curves, through animal/flock indices to include socio-economiccriteria. Inputs are focussed on limiting resources, common currencies of money ornutrient/energy used, and time standardised at one year. Net benefits of livestock to a householdare calculated by aggregating the value added by physical products (meat, manure, milk) to socioeconomicbenefits (saved interest/premium on credit/insurance) and deduction of purchasedinputs. The result is expressed as net benefit per unit of the most limiting resources: land, labour,and flock metabolic size. If these criteria chosen for the unit net benefit are appropriate, then theranking of the improved and indigenous livestock will reflect the choice of the farmer. Asubsequent paper will test this hypothesis in a dairy goat development project in the Ethiopianhighlands.